Interplay between noxious heat sensitivity and temporal summation magnitude in patients with fibromyalgia and long-term opioid use - Bao, Jason D.; Rosser, Morgan A.; Park, Su Hyoun; Baker, Anne K.; Martucci, Katherine T. (Frontiers in Neuroscience, 2023)
In chronic pain conditions such as fibromyalgia (FM), pain amplification within the central nervous system, or “central sensitization”, may contribute to the development and maintenance of chronic pain. Chronic pain treatments include opioid therapy, and opioid therapy may maladaptively increase central sensitization, particularly in patients who take opioids long-term. However, it has remained unknown how central sensitization is impacted in patients who use opioids long-term. To investigate how long-term opioid therapy affects central sensitization, we used the validated measure of temporal summation. The temporal summation measurement consists of applying a series of noxious stimuli to a patient’s skin and then calculating changes in the patient’s pain rating to each stimulus. Using this measurement, we evaluated temporal summation in study participants with fibromyalgia who take opioids long-term (i.e., greater than 90 days duration; n = 24, opioid-FM). We compared opioid-FM responses to 2 control groups: participants with fibromyalgia who do not take opioids (n = 33, non-opioid FM), and healthy controls (n = 31). For the temporal summation measurement, we applied a series of 10 noxious heat stimuli (sensitivity-adjusted temperatures) to the ventral forearm (2-second duration of each stimulus, applied once every 3 seconds). Additionally, we collected responses to standard pain and cognitive-affective questionnaires to assess pain severity and other factors. Group differences in sensitivity-adjusted stimulus temperatures were observed, with only the non-opioid FM group requiring significantly lower stimulus temperatures. (The opioid-FM group also required lower temperatures, but not significantly different from the control group.) However, all 3 groups exhibited similar magnitudes of temporal summation. Across combined FM groups, temporal summation negatively correlated with pain severity (r = -0.31, p = 0.021). Within the opioid-FM group, higher pain sensitivity to heat (i.e., lower sensitivity-adjusted temperatures) showed a trend relationship with higher opioid dosage (r = -0.45, p = 0.036), potentially reflective of opioid-related hyperalgesia. Our findings also indicated that heightened pain severity may skew sensitivity-adjusted temporal summation, thereby limiting its utility for measuring central sensitization. Overall, in participants taking opioids, temporal summation may be influenced by hypersensitivity to heat pain, which appeared to vary with opioid dosage.